Five new species of Myrsidea Waterston (Phthiraptera: Menoponidae) from tanagers (Passeriformes: Thraupidae) in Panama - Price, Roger D.; Johnson, Kevin P. (Zootaxa, 2009)
There are 23 species of Myrsidea recognized from passerine thraupid hosts. Five new species parasitic on members of this avian family are described. They and their type hosts are Myrsidea rozsai ex the Thick-billed Euphonia, Euphonia laniirostris d'Orbigny & Lafresnaye, M. cruickshanki ex the Carmiol's Tanager, Chlorothraupis carmioli (Lawrence), M. patersoni ex the Grey-headed Tanager, Eucometis penicillata (Spix), M. pagei ex the Crimson-backed Tanager, Ramphocelus dimidiatus Lafresnaye, and M. valimi ex the Tawny-capped Euphonia, Euphonia anneae Cassin. The first species is placed in the bonariensis species group, while the remaining four are placed in the fusca species group. Sequences of a portion of the mitochondrial cytochrome oxidase I (COI) gene were compared to other species of Myrsidea and were highly divergent.